3d-9=5d-11.

Simple and best practice solution for 3d-9=5d-11. equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3d-9=5d-11. equation:



3d-9=5d-11.
We move all terms to the left:
3d-9-(5d-11.)=0
We add all the numbers together, and all the variables
3d-(5d-11)-9=0
We get rid of parentheses
3d-5d+11-9=0
We add all the numbers together, and all the variables
-2d+2=0
We move all terms containing d to the left, all other terms to the right
-2d=-2
d=-2/-2
d=1

See similar equations:

| y/12+5=-19 | | 8(3-x)=2x+5 | | x•11=73 | | -9x-4=-11 | | -4x=29-5 | | 12/32=x/20 | | 12+3x=0.5x-8 | | 2x(x+1)-2=2(x-2)(x+3) | | -42-11x+15x=94 | | 2(p-10)=14 | | V=3.14(8.5/2)^2x12 | | 3x-x^2=-54 | | -45+12x-6x=93 | | -35=-9x+2x | | 3j^2+16j+13=0 | | 5.5x32=57 | | 6y+8=5y+8 | | 12•n=3 | | 36=-3(n+10) | | 4y−y+11=38 | | 1/2x+3=5/8x-1 | | -16=4(d+6) | | |p+3|=10 | | 3(1-3v)=-4(2v-3) | | 6y-9=9y-4y | | |2t+3|+2=9 | | 2(x+)=3x-1 | | 32=5n+4 | | -3=3x-6x | | 3(x+5)-5x=2(-4x+8) | | -38-4r=-7(8r-2) | | -3-6p=9 |

Equations solver categories